Polak na Antylach – Kazimierz Lux i jego opisanie San Domingo - Zajkowska, Joanna (Colloquia Litteraria, 2023)
The article discusses Kazimierz Lux’s travel entitled The description of the island of San-Domingo, which was published „Biblioteka Warszawska” in 1854 (v. 4, p. 197– 223). It is a paraliterary notation of the stay of the „Polish pirate” in the Antilles, where, as a soldier of the French 114 th brigade formed by Napoleon, he suppressed the slave uprising. Lux’s text is a fairly detailed study of San-Domingo’s climatic, geographical and living conditions, plant crops and livestock; however, above all, it is a fascinating record of a Pole’s encounter from the early nineteenth century with the exoticism of the second hemisphere